2000
DOI: 10.2307/2648233
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Demographic Trends in Teenage Fertility, 1980-1995

Abstract: Programs to further reduce the teenage birthrate should take into account the role of family stability, parent-child communication, sex education programs and engagement in school, as well as attempt to reduce the proportion of adolescents having sex at an early age and to improve contraceptive use. The increasing risk levels among sexually experienced teenagers suggest that current programs may be reducing sexual activity among adolescents already at a low risk of a teenage birth, without addressing the needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 13 publications
5
51
0
5
Order By: Relevance
“…The study by Davies et al (2006) indicated that the use of contraceptives has increased amongst adolescents in recent years. Whereas Manlove, Terry, Gitelson, Pappilo and Russel (2000) said that the consistent reliance on effective forms of contraception remains low. Reasons for inconsistent contraceptive use are not easily characterised as they are diverse and complex (Davies et al 2006).…”
Section: Introduction Problem Statementmentioning
confidence: 99%
“…The study by Davies et al (2006) indicated that the use of contraceptives has increased amongst adolescents in recent years. Whereas Manlove, Terry, Gitelson, Pappilo and Russel (2000) said that the consistent reliance on effective forms of contraception remains low. Reasons for inconsistent contraceptive use are not easily characterised as they are diverse and complex (Davies et al 2006).…”
Section: Introduction Problem Statementmentioning
confidence: 99%
“…Rates of teenage childbearing are especially high for girls who report first sexual intercourse during their early teen years (Manlove et al, 2000). One in seven girls report having sexual intercourse before age 15 (National Campaign to Prevent Teen Pregnancy, 2005) among whom, approximately one in seven have also been pregnant (Albert et al, 2003).…”
mentioning
confidence: 99%
“…Between 1990 and 2001, birth rates declined from 60 to 46 births per 1 000 girls aged 15-19 years (8). Factors associated with this decrease include positive changes in family environment, improvement in maternal education, stabilization in the proportion of teenagers having sex at an early age, and improved contraceptive use at first intercourse (7).…”
mentioning
confidence: 99%
“…In the United States of America, birth rates among adolescents have decreased since 1970 (7). Between 1990 and 2001, birth rates declined from 60 to 46 births per 1 000 girls aged 15-19 years (8).…”
mentioning
confidence: 99%